Recent advances in biosurfactant-based association colloids—Self-assembly in water - Hellweg, Thomas; Sottmann, Thomas; Oberdisse, Julian (Frontiers in Soft Matter, 2023)
Recent studies of self-assembly in binary systems of bio-surfactants, either of microbial origin or saponins extracted from plants, are reviewed. Saponins in water reported in the first section include aescin, glycyrrhizin, and quillaja saponins, while rhamnolipids are discussed in the second section on microbial surfactants. Studies of surface activities are a natural starting point of the characterization of surfactants, but here we focus mainly on physico-chemical and structural properties of self-assembled bulk structures in solution, often characterized by scattering techniques. When quantitative modelling is performed, self-assembly parameters like aggregation numbers, head group areas, and resulting shapes can be followed as a function of physical-chemical parameters like concentration, composition, temperature, or pH. Morphologies include micelles and their structural evolution with addition of other bio- or synthetic surfactants, co-surfactants, proteins or phospholipids.